MANAJEMEN KONFLIK AGRARIA STUDI KASUS DESA TANGUN KECAMATAN BANGUN PURBA KABUPATEN ROKAN HULU TAHUN 2012-2013 - Rangga Pati Liandra; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
In human life it is known that the land will not be separated from all human behavior because the land itself is a place for people to live and continue his life. Therefore, the land becomes a thing that is required by every member of society, so often there is a dispute between neighbors. In the Customary Law, this land is a very important issue. The relationship between man and the land very closely, because the land as a human being to live and continue his life.In this study the authors used qualitative research methods. Qualitative research is used in normal circumstances (natural setting) and data collected are generally qualitative. This qualitative research methods to understand and interpret the meaning of an event interaction of human behavior in a particular situation from the perspective of their own research.In 2010, a meeting between residents, PT. SSL, local officials and police. It aims to find the best solution so that this conflict can be resolved with good and peaceful. But over time until now there is no progress regarding this conflict. Only ever made by the community for the winning team Tangun village customary land isProblems that occur in dispute rural areas in Riau province are common and quite complicated because both sides are fighting over land has a special reason and we can not judge who is wrong directly. Because those who entrusts the land is the owner of the land, and those who have been entrusted to maintain, care for, and also uses the land within a certain period.Keywords: Conflict Management, Agricultural, Village Tangun